Unveiling Mobile Wallet Adoption: Exploring UTAUT's Influence on Behavioral Intentions - Thilagaraj.A , Dr.; V, Janani; B, Dr. Prem Anand; C, Dr. Fredrick Jorgenson; Sankaran, Dr. M. (South Eastern European Journal of Public Health, 2024)
In today’s world, smartphones have become the most important part of life. It has changed the lifestyles of many people. In recent times, the usage of smartphones has increased dramatically as it offers various benefits to its users. The rapid evolution of digital payment technologies has propelled the emergence of mobile wallets as a convenient and potentially transformative means of financial transactions. The current research focuses on analyzing the effects of UTAUT on users’ behavioral intentions for using Mobile wallet technology. In this empirical study, the main concepts of the UTAUT model are explained. Adopting the UTAUT framework, the survey evaluates important factors that influence users' intentions to adopt mobile wallets. This study uses survey data from 110 Internet users, which will be examined using regression, correlation, and weighted mean analysis. This research revealed positive significant correlation between intention and performance expectations, effort expectations, social norms, and privacy. However, it was also found that performance expectation, effort expectation and privacy of personal information had a significant positive influence on behavioral intention.